At the serpentine. - Serpentine Gallery, London (Edinburgh : Graeme Murray Gallery, 1984)
Ackling, Roger ; Charlton, Alan ; Cocker, Douglas ; Cooper, Thomas Joshua ; Cramb, James ; Finlay, Ian Hamilton ; Fulton, Hamish ; Parker, Evan ; Renouf, Edda ; Rückriem, Ulrich
Graeme Murray Gallery at the Serpentine, Serpentine Gallery, London, 6-28 October 1984
boek